Research in the sociology of work. (Greenwich, Conn. JAI Press, 1981)
Annual
v. 5. 1995 The meaning of work -- v.11. Labor revitalization : global perspectives and new initiatives / edited by Daniel B. Cornfield, Holly J. McCammon.
"A research annual."
Each issue for 1983- has also a distinctive title.
None published, 1982, 1984, 1986-1987.
Sociological abstracts
Keywords: Industrial sociology -- Periodicals; Industrial relations -- Periodicals; Industry -- Social aspects -- Periodicals; Labor -- Periodicals